Pembelajaran Materi Aritmetika Sosial Dengan Pendekatan STEM - Musdayati; Betty Heryuriani (Jurnal Inovasi Matematika, 2020)
The social arithmetic skill of students in mathematics is still poor required practice in-class learning. One of them provides learning through STEM approach (Science, Technology, Engineering, and Mathematics). This research leads to describe the improvement of students’ learning outcomes in social arithmetic material through the STEM approach. The classroom action research method carried out in two cycles was used in this study due to an improvement in students’ social arithmetic skills. The subjects in this study were 41 students of grade VII who was studying social arithmetic material. Learning activities were designed through the STEM approach by giving project tasks in making fermented cassava and banana chips. Data collection in this study was conducted through a written test for cognitive assessment, while for the affective evaluation seen from the preparation until the final project assignments report. The data analysis of the test was measured using descriptive quantitative and the data observation was evaluated using descriptive qualitative. The findings show that the STEM approach allows students to grasp the social arithmetic material that can be seen from better learning outcomes from the research subjects.